High mobility 2-dimensional electron gas at LaAlO3/SrTiO3 interface prepared by spin coating chemical methods. (26th September 2017) - Khan, Tahira; Zhang, Hui; Zhang, Hongrui; Yan, Xi; Hong, Deshun; Han, Furong; Chen, Yuansha; Shen, Baogen; Sun, Jirong
Abstract: Highly mobile 2-dimensional electron gases (2DEGs) at the (001), (011) and (111)-oriented LaAlO3 /SrTiO3 (LAO/STO) interfaces are obtained using spin coating chemical method, which is a gentle technique without plasma bombardment of the pulsed laser deposition. As revealed by x-ray diffraction spectrum and x-ray reflectivity analysis, the LAO over layer is epitaxially grown, and has a uniform thickness of ∼15 nm, ∼20 nm and ∼26 nm for (001), (011) and (111) orientations, respectively. The interfaces are well metallic down to 2 K. The carrier mobilities are ∼28 000 cm 2 V −1 s −1, ∼22 000 cm 2 V −1 s −1 and ∼8300 cm 2 V −1 s −1 at 2 K for the (001), (011) and (111) LAO/STO interfaces, respectively, and ∼8 cm 2 V −1 s −1, ∼4 cm 2 V −1 s −1 and ∼4 cm 2 V −1 s −1 at room temperature. The present work shows that the spin coating chemical method is a feasible approach to get high quality 2DEG at both the polar/non-polar and polar/polar interfaces.